Fundamental of zero trust among digital employees in migration to industry 4.0: Cyber security and movement to iot in Malaysian perspectives - Irza Hanie, Abu Samah; Intan Maizura, Abd Rashid; Abdul Shukor, Shamsudin; Wan Ahmad Fauzi, Wan Husain; Mohammad Harith, Amlus; Hariri, Hamzah (AIP Publishing, 2023)
Malaysia is now approaching towards Industrial 4.0. Many initiatives are taken by the government to improve in this digital era. 18.2% contribution towards country’s growth domestic product was achieved in 2016 through digital economy which was targeted in 2020 (Malaysia Digital Economy Corporation, 2018). This showed a positive sign that the world is accepting the era of digital technologies in many of the industries including in healthcare. The objective of this research is to determine the factor influencing zero-trust among employees in using technologies in healthcare sector. This research proposed a conceptual framework on Zero trust model for digital employees. The contribution in this research is that it may help Malaysian Productivity Corporation have some information that will be useful to Industry4WRD Readiness Assessment. Furthermore, this research hopes will give insight for Malaysia’s National Applied Research and Development Centre (MIMOS) for National Internet of Things Strategic Roadmap.